Phase separation drives the formation of biomolecular condensates in the immune system - Wen, Yuqing; Ma, Jian (Frontiers in Immunology, 2022)
When the external conditions change, such as the temperature or the pressure, the multi-component system sometimes separates into several phases with different components and structures, which is called phase separation. Increasing studies have shown that cells condense related biomolecules into independent compartments in order to carry out orderly and efficient biological reactions with the help of phase separation. Biomolecular condensates formed by phase separation play a significant role in a variety of cellular processes, including the control of signal transduction, the regulation of gene expression, and the stress response. In recent years, many phase separation events have been discovered in the immune response process. In this review, we provided a comprehensive and detailed overview of the role and mechanism of phase separation in the innate and adaptive immune responses, which will help the readers to appreciate the advance and importance of this field.